Effectiveness of lactic acid bacteria to increase the body resistance of common carp, Cyprinus carpio Linnaeus, 1758 against Aeromonas hydrophila - Rosidah Rosidah; Yuniar Mulyani; Fittrie Mellianawaty Pratiwy; Afifah Shabirah; Juli A Sinaga (Jurnal Iktiologi Indonesia, 2021)
This study aims to find out the right lactic acid bacteria (LAB) isolates to improve the common carp body's immune system against the attack of the Aeromonas hydrophila bacterium. Lactic Acid Bacteria (LAB) isolates were obtained from the organs of the common carp intestine. The study used a Completely Randomized Design consisting of four treatments and three replications. The treatment used was immersion of test fish for 24 hours in several isolates of LAB with a density of 108 cfu ml-1, namely A: without LAB isolate (control), B: isolate CcB7, C: isolate CcB8, D: isolate CcB15. Immersion is done three times with a frequency of seven days. Parameters observed included clinical symptoms, survival rate, red and white blood cell counts. The results showed the immersion of LAB isolate CcB15, namely Lactobacillus gasseri was most effective for increasing the body's resistance to Common Carp, which was demonstrated by mild clinical symptoms and faster recovery, high fish survival rate (83.33%), and number of cells the highest white blood count of 147,47x103 cell mm-3 (an increase in white blood cells by 38%). Abstrak Penelitian ini bertujuan untuk menentukan isolat bakteri asam laktat (BAL) yang tepat untuk meningkatkan daya tahan tubuh ikan mas terhadap serangan bakteri Aeromonas hydrophila. Isolat Bakteri Asam Laktat (BAL) diperoleh dari organ usus ikan mas. Penelitian menggunakan Rancangan Acak Lengkap yang terdiri atas empat perlakuan dan tiga ulangan. Perlakuan yang digunakan adalah perendaman ikan uji selama 24 jam pada beberapa isolat BAL dengan kerapatan 108 cfu ml-1 yaitu A: isolat tanpa BAL (kontrol), B: isolat CcB7, C: isolat CcB8, D: isolat CcB15. Perendaman dilakukan tiga kali dengan frekuensi tujuh hari. Parameter yang diamati meliputi gejala klinis, tingkat sintasan, jumlah sel darah merah dan putih,. Hasil penelitian menunjukkan bahwa perendaman isolat BAL CcB15 yaitu Lactobacillus gasseri paling efektif untuk meningkatkan daya tahan tubuh terhadap ikan mas, yang ditunjukkan dengan gejala klinis ringan dan pemulihan lebih cepat, tingkat sintasan ikan tinggi (83,33%) dan jumlah sel tertinggi. jumlah darah putih 147,47x103 sel mm-3 (peningkatan sel darah putih sebesar 38%).